Study on the Implications of the Function and Role of Urban Areas on Population Projections in the Formulation of Detailed Spatial Planning (RDTR) - Nasution, Anthony P; Karenina, Anna; Lestari, Forina (BHUMI: Jurnal Agraria dan Pertanahan, 2023)
The initial and crucial stage in the spatial planning process involves identifying the function and role of a region or area. This step sets the course, establishes goals, and defines the parameters for the subsequent spatial arrangement planning. Currently, the expedited development of Detailed Spatial Planning in Indonesia is closely tied to the function and role of an area, which is influenced by numerous factors that require careful consideration. This study aims to compare population projections using conventional projection methods with projections that take into account the functions and roles of the region. This study uses population projection analysis, population development scenarios, and spatial availability analysis to assess the differences in spatial projections that can accommodate population growth. The calculations unveiled a significant disparity between population-based projections and projections that consider the functions and roles of a city/area. This input is crucial for assessing spatial needs and the necessary infrastructure and supporting facilities that will be incorporated in the formulation of the structure and spatial patterns of Detailed Spatial Planning. Hence, when estimating population projections, it is essential for planners to consider projections that incorporate the functions and roles carried out by the area.